DETECTION METALLO-BETA-LACTAMASE GENE IMP-1 AND IMP-2 OF Pseudomonas aeruginosa CLINICAL ISOLATES IN SANGLAH HOSPITAL BALI - Tarini, Ni Made Adi; Fatmawati, Ni Nengah Dwi; Mayura, I Putu Bayu (International Journal of Biosciences and Biotechnology; Vol 3 No 1 (2015))
Pseudomonas aeruginosa is a pathogen frequently found as an agent of Hospital Acquired infections. This bacterium is very easy to be resistant to several types of antibiotics through various mechanisms. Carbapenem such as Imipenem and Meropenem is a potential option for the therapy of this bacterium, but unfortunately P. aeruginosa has ability in hydrolyzing these antibiotics through enzyme metallo-?-lactamases (MBLs). Recently, IMP and VIM, MBLs enzyme group are reported common from various countries, but no data is reported for these enzymes in Indonesia especially in Bali. In fact, the resistant data of P. aeruginosa against carbapenem group antibiotics such as meropenem and imipenem is quite high in Sanglah General Hospital in 2014 was 35% and 45% respectively. Therefore, the aim of this study was to detect IMP-1 and IMP-2 genes of MDR P. aeruginosa, which are phenotypically resistant to the antibiotic Imipenem and Meropenem disks based on CLSI standards in Clinical Microbiology Laboratory, Sanglah General Hospital, Denpasar, Bali. Eighty-six isolates were isolated from sputum (25 / 29.1%), wound (25 / 29.1%), urine (15 / 17.4%),endotracheal Tube (11 / 12.8), pus (6/7% ), blood (3 / 3.5%) and tissue (1 / 1.1%). In this study, all isolates were subjected to PCR for detection of IMP-1 and IMP-2. The result showed that 9 isolates were positive IMP-1 gene (10.5%), but there was no isolate positive for IMP-2 gene. The result was similar with that of the other countries, especially for the gene IMP-1. Detection and molecular characterization of MBL-producing P. aeruginosa strains are very important for infection control purposes. Currently, this study is still continued for detection of another MBL genes.
Keywords: Pseudomonas aeruginosa, MBLs gene, PCR, Positive Control